Mobile Learning for Mathematics (Mathematics Solver Application) - Malcolm Ligong, July (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Mathematics is one of core subject that student have to learn in school. However, learning mathematics need lots of time to study as students have to do lots of exercise to do well in mathematics. This project give solution on helping student to learn mathematics outside the school with help learning application. The application have function to scan the questions using camera, drawing board to write the questions and text field to type the questions. However, for using functionality of the scanning the questions using camera only work for printed questions as the application cannot recognised the handwriting while drawing board to write the questions can be used as remove the image noises when using the camera to scan the questions. The answer of the questions will be shown after the user click calculate button.